Peran Guru PPKN dalam disiplin Siswa Madrasah Thafizhil Quran dalam Pengembangan Mata Pelajaran Pancasila dan Pendidikan Kewarganegaraan - Arnifelis Gulo; Pulung Sumantri; Latifah Hanum; Hadiani Fitri (Universitas Islam Sumatera Utara, 2022)
The point of this exploration is to figure out how PPKn instructors at MA Thafizhil Quran impact understudy conduct. Unmistakable subjective exploration was utilized in this examination. All PPKn educators and understudies who disregarded the guidelines at Mama Thafizhil Quran became research subjects. Perception, meetings, and documentation are strategies for information assortment. Information decrease, information show, and information confirmation are three information investigation strategies. As per the discoveries of this examination, the job of PPKn educators in shaping understudy discipline at MA Thafizhil Quran is to give understudies a comprehension of discipline and increment discipline with the goal that understudies don't disrupt the norms. With respect to pretended by PPKn educators in empowering understudy discipline at MA Thafizhil Quran, they do this by demonstrating conduct like discipline, obligation and authority.